Wikstroemia: A Review on its Phytochemistry and Pharmacology - Huan, Duong Q.; Hop, Nguyen Quang; The Son, Ninh (Current Pharmaceutical Biotechnology, 2024)
Background: Wikstroemia (the family Thymelaeaceae) consists of medicinal plants which established great value in traditional medicines for many years. For instance, W. indica is always recommended for treatments of syphilis, arthritis, whooping cough, and cancer. No systematic review of bioactive compounds from this genus has been recorded to date. Objectives: The objective of the current study is to review phytochemical investigations and pharmacological effects of Wikstroemia plant extracts and isolates. Methods: By searching on the internet, the relevant data about Wikstroemia medicinal plants were retrieved from internationally renowned scientific databases, such as Web of Science, Google Scholar, Sci-Finder, Pubmed, and so on. Results: More than 290 structurally diverse metabolites were separated and identified from this genus. They include terpenoids, lignans, flavonoids, coumarins, mono-phenols, diarylpentanoids, fatty acids, phytosterols, anthraquinones, and others. Pharmacological records indicated that Wikstroemia plant crude extracts and their isolated compounds bring out various beneficial effects, such as anticancer, antiinflammatory, anti-aging, anti-viral, antimicrobacterial, antimalarial, neuroprotective, and hepatoprotective activities. Conclusion: Wikstroemia has been regarded as a worthy genus with numerous phytochemicals and various pharmacological potentials. Modern pharmacological studies have successfully provided evidence for traditional uses. Nonetheless, their action mechanisms need to be further investigated. Although various secondary metabolites were identified from Wikstroemia plants, the current pharmacological research mainly concentrated on terpenoids, lignans, flavonoids, and coumarins.
Keywords: phytochemistry